Morphology and molecular phylogeny of Macrobrachium suphanense sp. nov. (Decapoda: Palaemonidae) from Thailand - Saengphan, Nukul; Panijpan, Bhinyo; Senapin, Saengchan; Laosinchai, Parames; Ruenwongsa, Pintip; Suksomnit, Auaree; Phiwsaiya, Kornsunee (Zootaxa, 2018)
A small freshwater prawn in Thailand has been found to be a new species and is named Macrobrachium suphanense (Decapoda: Palaemonidae). Fully grown male M. suphanense appeared very different from the most closely related male of M. sintangense: size smaller, second pereiopod smaller and less robust, rostrum form different and, in females, fewer eggs. Less closely related, fully grown M. dolatum has sharper distal cutting edge on fixed finger and M. hungi has longer rostrum than M. suphanense. DNA analyses put M. suphanense, M. sintangense and M. nipponense in the same clade with M. nipponense sister to the other two. Two more clades consist of M. dienbienphuense and M. niphanae on the one hand and M. lanchesteri and M. rosenbergii on the other. The relationship among the three clades is not clearly resolved.